Transverse Coupled Cavity VCSELs: Bridging Ultrabroadband Dynamics to Optical Supermodes - Martino D'Alessandro; Valerio Torrelli; Francesco Bertazzi; Michele Goano; Nikolay N. Ledentsov; Markus Lindemann; Mariangela Gioannini; Pierluigi Debernardi; Alberto Tibaldi (IEEE Photonics Journal)
In this work we investigate the ultrabroadband dynamics of transverse coupled cavity VCSELs. This study is based on a multimode rate equation model, whose parameters are directly provided by a full-wave vectorial electromagnetic solver. This approach sets a step towards the comprehensive physics-based modeling of transverse-coupled cavity VCSELs, providing a relation between the features of the optical supermodes and the enhancements of the intensity modulation response. The approach emphasizes how the bandwidth enhancement, ascribable to a photon-photon resonance picture, can be triggered by forcing asymmetries in the bias and modulation contacting scheme of the device, and the importance of collecting the fields from each single cavity, providing an interpretation of recent experimental observations and paving the way towards more systematic design strategies.